2012
DOI: 10.1007/s10856-012-4660-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biomechanical characterizations of porcine myocardial extracellular matrix

Abstract: Extracellular matrix (ECM) of myocardium plays an important role to maintain a multilayered helical architecture of cardiomyocytes. In this study, we have characterized the structural and biomechanical properties of porcine myocardial ECM. Fresh myocardium were decellularized in a rotating bioreactor using 0.1 % sodium dodecyl sulfate solution. Masson’s trichrome staining and SEM demonstrated the removal of cells and preservation of the interconnected 3D cardiomyocyte lacunae. Movat’s pentachrome staining show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 67 publications
2
67
0
1
Order By: Relevance
“…41 . As shown in our previous publications, 38, 39 we have developed an optimal decellularization protocol to generate 3D porcine acellular myocardial scaffolds, in which 3D cardiomyocyte lacunae and ECM networks were well preserved along with mechanical anisotropy and vasculature templates; 38, 39 the acellular myocardial scaffolds also showed good stem cell recellularization and differentiation potential and experienced positive tissue remodeling manifested by a recovering trend in tissue mechanical properties. 38 …”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…41 . As shown in our previous publications, 38, 39 we have developed an optimal decellularization protocol to generate 3D porcine acellular myocardial scaffolds, in which 3D cardiomyocyte lacunae and ECM networks were well preserved along with mechanical anisotropy and vasculature templates; 38, 39 the acellular myocardial scaffolds also showed good stem cell recellularization and differentiation potential and experienced positive tissue remodeling manifested by a recovering trend in tissue mechanical properties. 38 …”
Section: Introductionmentioning
confidence: 87%
“…39 Forty fresh pig hearts were harvested from ∼6-month old pigs and transported from the local slaughter house to our laboratory in phosphate Buffered Saline at 4 °C. From the middle region of the anterior left ventricular wall, we were able to trim square-shaped myocardium samples (20 × 20 × ∼3 mm), of which one edge aligned along the muscle fiber preferred direction (PD) and the other edge aligned along the cross-fiber preferred direction (XD); note that the PD direction was determined based on overall muscle fiber texture and heart anatomy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the properties of the normal myocardium are dominated by the structure and orientation of the myocytes, the properties of the infarct region are primarily governed by the network of newly deposited collagen fibers [3, 8]. Biaxial mechanical testing is the gold standard for testing planar anisotropic materials, making this method ideal for studying how variations in the properties of the collagen network alter scar mechanics in a mouse MI model [7, 9, 10]. Biomechanical analysis of infarct tissue, therefore, provides a critical understanding of the complex interactions between ECM structure, LV function, and patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the engineered construct improved the infarcted tissue regeneration, evidenced by vascularization and cardiomyocytes differentiation in the implanted region. 124 Wang et al 76,125 and Godier-Furnemont et al 126 decellularized porcine (Figure 2A) and human myocardium and recellularized these acellular scaffolds with stem cells. Both studies found that the preservation of myocardial 3D ECM architecture and mechanical cues benefit cell proliferation, ingrowth, differentiation, tissue remodeling, and angiogenesis.…”
Section: Current Attempts In Establishing Early Functional Perfusmentioning
confidence: 99%